Syndromic testing as a diagnostic modality for gastrointestinal infection - Olivia Jocelyn; David Hutajulu; Erni Juwita Nelwan (International Journal of Biomedical Science and Travel Medicine, 2024)
Indonesia continues to grapple with sanitation issues, contributing to high incidence of gastrointestinal infections. Timely and accurate diagnosis is crucial to minimize the use of empirical antibiotics and medical expenses. Microbial culture, the current gold standard for diagnosing infections, has certain limitations in terms of duration and accuracy. There is a novel multiplex PCR (mPCR)-based diagnostic approach for infections called syndromic testing that can identify up to 20 pathogens simultaneously within 1–2 hours. This evidence-based case report aims to evaluate its sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) in diagnosing gastrointestinal infections. Literature search was conducted on February 21, 2024, across several databases which were PubMed, Scopus, Wiley Online Library, and ProQuest. Two prospective cross-sectional studies met the inclusion and exclusion criteria which were then critically appraised. Both studies measured the diagnostic accuracy of syndromic testing for Salmonella and Shigella, yielding sensitivity of 75–95.2%, specificity of >98%, PPV up to 88.2%, and NPV of >99%, indicating its good accuracy. Syndromic testing presents as a promising alternative diagnostic modality for infections, addressing the limitations of culture-based methods.